2008
DOI: 10.1136/bjsm.2008.052126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 weeks of moderate–intensity resistance training on arterial stiffness: a randomised controlled trial in women aged 32–59 years

Abstract: This study found that moderate-intensity resistance training did not increase arterial stiffness in middle-aged women, which may have great importance for health promotion with resistance training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
4
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 27 publications
6
108
4
9
Order By: Relevance
“…However, some studies suggest that high-intensity resistance training is associated with reduced major artery compliance and increased arterial stiffness [33][34][35]. On the other hand, current evidence suggests that low-to moderate-intensity resistance training does not effect on arterial stiffening [36][37][38]. Interestingly, resistance training results in decreased blood pressure as a training adaptation despite increases in blood pressure during exercise [39].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, some studies suggest that high-intensity resistance training is associated with reduced major artery compliance and increased arterial stiffness [33][34][35]. On the other hand, current evidence suggests that low-to moderate-intensity resistance training does not effect on arterial stiffening [36][37][38]. Interestingly, resistance training results in decreased blood pressure as a training adaptation despite increases in blood pressure during exercise [39].…”
Section: Discussionmentioning
confidence: 60%
“…However, although aerobic exercise effectively decreases arterial stiffness, it does not induce gains in strength and lean body mass, as well as increases in bone density compared with resistance training [4,41]. In contrast, resistance training increases [33][34][35] or does not alter [36][37][38] arterial stiffness compared with aerobic exercise. Therefore, prescribing aerobic and resistance training in combination is proposed as an efficacious strategy to improve cardiovascular as well as musculoskeletal functions in the elderly.…”
Section: Discussionmentioning
confidence: 89%
“…As far as we know, the effect of walking alone and quantitative investigation of physical activity on baPWV have not been previously reported. Most previous studies [10][11][12][13][14] measured the effect of supervised physical activity sessions using exercise facilities. For older people, visiting exercise facilities appears more difficult than walking.…”
Section: Discussionmentioning
confidence: 99%
“…Ryo Miyazaki 1,2,3) , Yoshikazu Yonei 1) , Yoriko Azuma 3) , Hitoshi Chiba 4) , Koichiro Hayashi 5) , Koji Yamatsu 6) previous studies assessed the effectiveness of physical activity programs on baPWV either using resistance training 9) or exercise at special facilities [10][11][12][13][14] . Such exercise programs are difficult for older people to complete at home without super vision.…”
Section: Relationship Between the Change In Daily Step Count And Bracmentioning
confidence: 99%
“…In contrast, CortezCooper et al (2008) reported that 13 weeks of moderate-intensity resistance training two or three times per week does not reduce central arterial compliance in middle-aged and older adults. In addition, Yoshizawa et al (2009) demonstrated that 12 weeks of moderateintensity resistance training did not affect arterial stiffness in middle-aged women. Moreover, low-intensity resistance training with short inter-set rest periods reduces arterial stiffness and improves vascular endothelial function (Okamoto et al, 2011).…”
Section: Resistance Exercise and Arterial Stiffnessmentioning
confidence: 99%